Evaluación del efecto de temperatura en el cultivo de hortalizas Lechuga crespa (Latuca sativa), Papa nabo (Brassica rapa), Nabo (Brassica napus), Bajo cubierta plástica y campo abierto en el campus CEASA, cantón Latacunga, provincia de Cotopaxi, 2021-2022. - Guangasig Chango, Aida Mariela (2022)
This research was conducted at the Technical University of Cotopaxi, Campus Salache, Faculty of Agricultural Sciences and Natural Resources in order to evaluate the effect of temperature on the cultivation of vegetables Lechuga crespa, (Lactuca sativa), Papanabo, (Brassica rapa) Turnip (Brassica napus) under plastic cover and open field. The specific objectives were: Determine the optimum temperature for the development of vegetable crops under plastic cover and open field; Define the best vegetable in terms of temperature. In order to develop and disseminate technologies to improve agricultural productivity of soil in high altitude areas, also called high altitude greenhouse; to achieve this we worked on three topics addressed with specific technical equipment, internal temperature memory, extractors, external and internal sensors, crop response to climatic variations, relationships under modified climate and harvest, functional quality for the differentiation of vegetables in their adequate harvest index. The study results revealed that temperature does influence the development and growth of agroecological vegetables; some crops are adapted to extreme temperatures, but require proper care for their production, in regions of high latitudes with a small increase in global average temperature, can benefit from climate change with an increase in soil productivity suitable for agriculture, also improve the soil with organic vegetation avoiding erosion.